Esporre il modernismo sovietico: dialogo con Aleksandra San'kova - Aleksandra San'kova; Emilio Mari (eSamizdat)
The interview with Alexandra Sankova is focused on the various stages of the Soviet Design history and, in particular, on the most representative and singular examples of the everyday objects.